Casim Coffee Business Development Strategy in Karangpring Village, Sukorambi District, Jember Regency - Utami, Bening; Ismail, Andi Muhammad (Jurnal Manajemen Agribisnis dan Agroindustri, 2024)
Casim Coffee Business, a microenterprise in Jember Regency, requires development to enhance its operations. This study aims to: (1) identify and analyze internal and externsal factors influencing the strengths, weaknesses, opportunities, and threats in the development of Casim Coffee Business in Karampling Village, Skollambi District, Jember Regency; (2) formulate alternative strategies for business development; and (3) determine strategic priorities for implementation. The study employs IFE Matrix, EFE Matrix, SWOT Analysis, and QSPM Matrix methodologies. The IFE Matrix yielded a score of 2.882, while the EFE Matrix scored 2.760. According to the IE Matrix, the business is positioned in cell V, which corresponds to a "Maintenance and Sustainment" strategy. SWOT analysis identified 10 alternative development strategies, and the QSPM Matrix prioritized participation in MSME bazaar events and raising product awareness to address the limited local market, with the highest attractiveness score of 6.917.